The Influence of Leadership Style, Psychological Work Environment, Perceived Organizational Support (POS) through Intrinsic Job Satisfaction on Behavior Organizational Citizenship Behavior ( OCB ) Non-Civil Servant Government Employee Education Staff (PPNPN) at Jember University - Fitri Hapsari; Markus Apriono; Purnamie Titisari (International Journal of Economics and Management Research, 2024)
Jember University is the largest academic community in the Jember region, East Java, which has 1,312 teaching and educational staff consisting of 544 educational staff . permanent/PNS (Civil Servants) and 768 contract education staff /PPNPN ( Non-Civil Servant Government Employees). Seeing the enormous potential of Jember University to develop rapidly, it is necessary to improve the quality of its human resources. Study This aim For analyze influence leadership style, psychological work environment, perceived organizational support (POS) through intrinsic job satisfaction on organizational citizenship behavior (OCB) of non-civil servant government employees (PPNPN) at the University of Jember. This research using explanatory research type . The population in this study was all PPNPN education staff that is as much 768 people with a research sample of 263 people. Technique taking sample in study This use method purposive sampling . Analytical tools used in this research use method analysis Structural Equation Model – Analysis of Moment Structure ( SEM- AMOS). The research results show that there is a significant influence between Leadership Style , Psychological Work Environment , Perceived Organizational Support (POS) on Intrinsic Job Satisfaction and Organizational behavior Citizenship Behavior (OCB). And intrinsic job satisfaction is able to mediate Leadership Style , Psychological Work Environment , and Perceived Organizational Support (POS) on Organizational behavior Citizenship Behavior (OCB)